If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3k + 4) * x + -1(2k + -6) * y = -10 Reorder the terms: (4 + 3k) * x + -1(2k + -6) * y = -10 Reorder the terms for easier multiplication: x(4 + 3k) + -1(2k + -6) * y = -10 (4 * x + 3k * x) + -1(2k + -6) * y = -10 Reorder the terms: (3kx + 4x) + -1(2k + -6) * y = -10 (3kx + 4x) + -1(2k + -6) * y = -10 Reorder the terms: 3kx + 4x + -1(-6 + 2k) * y = -10 Reorder the terms for easier multiplication: 3kx + 4x + -1y(-6 + 2k) = -10 3kx + 4x + (-6 * -1y + 2k * -1y) = -10 Reorder the terms: 3kx + 4x + (-2ky + 6y) = -10 3kx + 4x + (-2ky + 6y) = -10 Reorder the terms: 3kx + -2ky + 4x + 6y = -10 Solving 3kx + -2ky + 4x + 6y = -10 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-4x' to each side of the equation. 3kx + -2ky + 4x + -4x + 6y = -10 + -4x Combine like terms: 4x + -4x = 0 3kx + -2ky + 0 + 6y = -10 + -4x 3kx + -2ky + 6y = -10 + -4x Add '-6y' to each side of the equation. 3kx + -2ky + 6y + -6y = -10 + -4x + -6y Combine like terms: 6y + -6y = 0 3kx + -2ky + 0 = -10 + -4x + -6y 3kx + -2ky = -10 + -4x + -6y Reorder the terms: 10 + 3kx + -2ky + 4x + 6y = -10 + -4x + -6y + 10 + 4x + 6y Reorder the terms: 10 + 3kx + -2ky + 4x + 6y = -10 + 10 + -4x + 4x + -6y + 6y Combine like terms: -10 + 10 = 0 10 + 3kx + -2ky + 4x + 6y = 0 + -4x + 4x + -6y + 6y 10 + 3kx + -2ky + 4x + 6y = -4x + 4x + -6y + 6y Combine like terms: -4x + 4x = 0 10 + 3kx + -2ky + 4x + 6y = 0 + -6y + 6y 10 + 3kx + -2ky + 4x + 6y = -6y + 6y Combine like terms: -6y + 6y = 0 10 + 3kx + -2ky + 4x + 6y = 0 The solution to this equation could not be determined.
| 4a-8=8a-(4a+8) | | 2n+18=3n+37 | | x^2-14x+360=0 | | -10(10n-9)+6(-5n+7)= | | 310=3x-8(8x+7) | | 2(x+1)-1=11 | | c=38.34+0.50 | | 5x-2(x-3)=4x+15 | | 11d-10=6d | | N-6n= | | 4m^2n+(-m^2n)=0 | | 4m^2n+(-m^2n)= | | 0.1*x+0.25(5x)=5.25 | | log=0.45 | | 0.85x=612 | | (6x-10)+(6x+10)=18 | | 5(7x+1)=5+2x | | 2(x-7)+3x-1=4x+3 | | 2x+x+9x=3+35+2-4 | | 87b+17b= | | 20x-5x+4=15x-4 | | 25t=25t+5 | | 3x-a=b+a | | -81r+73r= | | g(x)=x^2+22x+12 | | 8x+5=2x-5 | | 7x+6=-12 | | 6a^2+19a+15= | | Y+z=108 | | 8-88n-45n= | | 42=2(x+3)+2(x-12) | | Y=(3x^2-3x+6)*2 |